Perspectives About Modulating Host Immune System in Targeting SARS-CoV-2 in India - Majumdar, Sreyashi; Verma, Rohit; Saha, Avishek; Bhattacharyya, Parthasarathi; Maji, Pradipta; Surjit, Milan; Kundu, Manikuntala; Basu, Joyoti; Saha, Sudipto (Frontiers in Genetics, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative agent of coronavirus induced disease-2019 (COVID-19), is a type of common cold virus responsible for a global pandemic which requires immediate measures for its containment. India has the world’s largest population aged between 10 and 40 years. At the same time, India has a large number of individuals with diabetes, hypertension and kidney diseases, who are at a high risk of developing COVID-19. A vaccine against the SARS-CoV-2, may offer immediate protection from the causative agent of COVID-19, however the protective memory may be short-lived. Even if vaccination is broadly successful in the world, India has a large and diverse population with over one-third being below the poverty line. Therefore, the success of a vaccine, even when one becomes available, is uncertain, making it necessary to focus on alternate approaches of tackling the disease. In this review, we discuss the differences in COVID-19 death/infection ratio between urban and rural India; and the probable role of the immune system, co-morbidities and associated nutritional status in dictating the death rate of COVID-19 patients in rural and urban India. Also, we focus on strategies for developing masks, vaccines, diagnostics and the role of drugs targeting host-virus protein-protein interactions in enhancing host immunity. We also discuss India’s strengths including the resources of medicinal plants, good food habits and the role of information technology in combating COVID-19. We focus on the Government of India’s measures and strategies for creating awareness in the containment of COVID-19 infection across the country.